Evaluation of three Bacillus spp. isolated from the gut of giant freshwater prawn as potential probiotics against pathogens causing Vibriosis and Aeromonosis - Sam-on, Muhamad Firdaus Syahmi; Mustafa, Shuhaimi; Yusof, Mohd Termizi; Mohd Hashim, Amalia; Abbasiliasi, Sahar; Zulkifly, Shahrizim; Jahari, Muhamad Amin; Roslan, Muhamad Akhmal Hakim (Elsevier, 2022)
Pathogens from the Vibrio and Aeromonas genera often cause detrimental effects to the aquaculture sector. Previously, antibiotics was used to resolve the infections, but this caused the spread of antibiotic resistant bacteria and antibiotic resistance genes into the environment. As an approach to address this issue, probiotic bacteria were introduced to improve the hosts' microbiome, disease protection, health condition, growth efficiency, feed consumption, stress response and general vigour. However, reports showed that some commercially available probiotics were restricted to a small number of microbial species and there are inconsistencies concerning its effectiveness. Hence, the aim of this study was to isolate and evaluate new Bacillus spp. from the gut of giant freshwater prawn as potential probiotics. Three Bacillus spp. isolates, Bacillus subtilis FS6 (MZ960135), Bacillus velezensis FS26 (MZ960133) and Bacillus pumilus FS97 (MZ960136) were characterised, and in vitro testing showed good probiotic properties which can help in dealing with diseases in aquaculture. Among the Bacillus spp., Bacillus velezensis FS26 showed higher antimicrobial activity towards Aeromonas hydrophila LMG 13658 and Aeromonas veronii clone DK-A. veronii-27 at 23.7 mm and 25 mm, respectively. Bacillus subtilis FS6 and Bacillus velezensis FS26 resulted in good adherence to both xylene and chloroform hydrocarbons. The Bacillus spp. isolated displayed high survivability towards 0.3% bile salt and exhibited amylase, protease, and lipase activities. Thus, the isolated Bacillus spp. are considered safe based on the sensitivity analysis towards antibiotics and γ-haemolytic activity.